Intussusception in adults: A rare presentation - Rao, Dr sonali (GMC Patiala Journal of Research and Medical Education, 2024)
Intussusception is a potentially fatal condition that happens when a section of the intestine bends like a telescope, with one segment slipping inside another. The proximal portion that telescopes into the intestine is known as the intussceptum, and the distal portion that receives the proximal portion is known as the intussuscipiens. This process can lead to multiple complications such as bowel obstruction, bowel necrosis/gangrene leading to sepsis. The disease process is much more common in the paediatric population and uncommon in adults, but when present is likely to be due to a pathological lead point such as benign or malignant masses